The Moderating Role of Emotional Intelligence in the Relationship between Organizational Compassion and Forgiveness Climate: Public vs. Private Education Institutions - Hajra Ahmad; Warda Ejaz; Adeela Anwar; Dr Ahmed Abdul Hameed (Social Science Review Archives, 2025)
The phenomena of interest in this study is to examine the relationship between organization compassion and forgiveness climate with moderating effect of emotional intelligence within the higher education institutions, within the study of both private and public educational institutes. This study investigates the impact of Organizational Compassion on forgiveness climate with the moderating role of Emotional Intelligence within both public and private sector educational institutions. Data were collected from a questionnaire with 220 valid responses from public and 216 from private sector educational institutions. Cronbach’s alpha and composite reliability tests were conducted to check data reliability, along with the Fornell-Larcker criterion for ensuring discriminant validity. The analysis was performed by using PLS-SEM through Smart PLS 4.0, for both direct and moderating effects. The results indicate a significant positive relationship between Organizational Compassion and forgiveness climate in both sectors. Furthermore, emotional intelligence provided positive moderating strength to this relationship to amplify the effect of Organizational Compassion on forgiveness climate. These insights offer practical implications for educational leaders and policymakers, emphasizing the importance of cultivating compassion and emotional intelligence to improve institutional culture, collaboration, and emotional well-being. The prior research has explored the phenomena of compassion and forgiveness, but a significant gap persists in exploring how organization compassion fosters a forgiveness climate with reference to academic setting. This study also contributes novel insight by studying Emotional intelligence as a moderator between these variables. It also distinguishes between public and private academic institutes, contributing to sector specific organization research.